PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.1 SMP NEGERI 5 TELUK KUANTAN - Lestaria Meri; Atma Murni; Syofni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract: This research was based on the students achievement in learning mathematics especially grade VII.1 of SMPN 5 Teluk Kuantan under the Mastery Minimum Criteria with percentage of 44.8% on the subject matter about fractions. The research conducted was the Classroom Action Research. The aims of this research is to improve the learning process and results on the students learning mathematic by implementing cooperative learning model structural approach of Numbered Heads Together. There were 29 students in the class consisting 22 boys and 7 girls as the participant of this research. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students’ Mathematic tests were analyzed in quantitative desciptive. The qualitative desciptive showed an improvement of learning process prior to the action on the first and second cycles.. The results of this research showed an increasing number of students learning Mathematic from the basic score with percentage 44,8% to 58,6% on the first test and 82,7% on second test. Based on the result of this research could be concluded that the implementation of Cooperative Learning Model structural approach of Numbered Heads Together can improve the students’ achievement of learning Mathematic in grade VII.1 of SMPN 5 Teluk Kuantan in the second semester academic years 2014/2015.Keywords: Students Math Achievement, Cooperative Learning Model Structural Approach of Numbereed Heads Together, Clasroom Action Research.